2021
DOI: 10.3233/cbm-200316
|View full text |Cite
|
Sign up to set email alerts
|

MCM5 urine expression (ADXBLADDER) is a reliable biomarker of high-risk non- muscle-invasive bladder cancer recurrence: A prospective matched case-control study

Abstract: BACKGROUND: Mini Chromosome Maintenance 5 (MCM5) is considered as a urinary biomarker of bladder cancer. ADXBLADDER is a commercially available test to detect MCM5 antibodies. OBJECTIVE: External validation of ADXBLADDER test as a urinary biomarker of histopathologically confirmed non-muscle invasive bladder cancer (NMIBC) recurrence. METHODS: The study enrolled 119 consecutive patients with a history of NMIBC and 37 healthy volunteers matched as controls. Single, full-void urine samples were collected from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Twenty-one studies, comprising 7330 patients, were included in the quantitative synthesis. All the studies included in the quantitative synthesis reported on the diagnostic value of UBTs for the detection of recurrence during surveillance: ten studies on Xpert bladder cancer [17][18][19][20][21][22][23][24][25][26], five studies on Bladder EpiCheck [26][27][28][29][30], three on Adxbladder [31][32][33], two on Uromonitor [34,35], and two on Cxbladder Monitor [36,37].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one studies, comprising 7330 patients, were included in the quantitative synthesis. All the studies included in the quantitative synthesis reported on the diagnostic value of UBTs for the detection of recurrence during surveillance: ten studies on Xpert bladder cancer [17][18][19][20][21][22][23][24][25][26], five studies on Bladder EpiCheck [26][27][28][29][30], three on Adxbladder [31][32][33], two on Uromonitor [34,35], and two on Cxbladder Monitor [36,37].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The prevalence of disease for each UBT is reported in Table 1. The pooled recurrence rate was calculated at 18%, with significant heterogeneity across studies with rates ranging from 6% [36] up to 70% [32].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some studies, pTa low-grade cases were regarded as negative for BCa, increasing, therefore, NPV. Nevertheless, according to these results, a negative test could indicate the absence of the recurrence [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“… 33 MCM5 urine expression had moderate sensitivity to detect non-muscle invasive relapse and could correctly diagnose T1 stage relapse or high-grade tumor. 34 Immunocytochemistry with MCM5 antibodies from urine can improve the ability of urinary cytology to detect urothelial carcinoma of the bladder. 35 Another study also indicated that MCM5 was a novel biomarker for the diagnosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%